Unveiling the immunosuppressive landscape of pancreatic ductal adenocarcinoma: implications for innovative immunotherapy strategies - Guo, Songyu; Wang, Zhenxia (Frontiers in Oncology, 2024)
Pancreatic cancer, particularly pancreatic ductal adenocarcinoma (PDAC), stands as the fourth leading cause of cancer-related deaths in the United States, marked by challenging treatment and dismal prognoses. As immunotherapy emerges as a promising avenue for mitigating PDAC's malignant progression, a comprehensive understanding of the tumor's immunosuppressive characteristics becomes imperative. This paper systematically delves into the intricate immunosuppressive network within PDAC, spotlighting the significant crosstalk between immunosuppressive cells and factors in the hypoxic acidic pancreatic tumor microenvironment. By elucidating these mechanisms, we aim to provide insights into potential immunotherapy strategies and treatment targets, laying the groundwork for future studies on PDAC immunosuppression. Recognizing the profound impact of immunosuppression on PDAC invasion and metastasis, this discussion aims to catalyze the development of more effective and targeted immunotherapies for PDAC patients.